Penerapan Bauran Promosi Pada Saluran Distribusi Bagi Produk UMKM Di Kota Padang - Erna Susanti; Dimas Perdana Oskar (EKONOMIKA SYARIAH : Journal of Economic Studies, 2019)
Souvenirs shop plays important part in selling and introducing the SME’s product. This research purpose are to understand and to identify of how the souvenirs shop in Padang deal in the application of integrated promotional mix. This study uses qualitative descriptive method to 10 souvenirs shop in Padang, Padang Culture and Tourism Office, Padang Cooperatives and SME’s Office, and ASITA West Sumatra. Data collection method used were in-depth interview and focus group discussion. Their understanding in integrated promotional mix are identically expensive and have no direct impact in trading which this research try to change that mislead understanding. In general, the promotion mix that they do is using visual media in the form of bilboard for advertsing, for sales promotion by providing product samples, giving discounts dan brochures. The ability of the resources owned which is still limited and still depends on the programs from related offices for the promotion of teir products.